Hegemony of economic values in conducting clinical trials with a placebo-control group to investigate the treatment of periodontitis in lower-middle-income countries (2021)
This article analyzes the bioethical implications of using a control/placebo group when conducting clinical trials (CTs) investigating the treatment of periodontitis. For this, the deductive method was used, proposing the interrelation of values, and a scoping systematic review was carried out. A total of 53% of the CTs reviewed were performed in low- and middle-income (LMI) countries, and 92% used a control/placebo group as a comparison group. Although there is a gold standard for the adjunctive treatment of periodontitis, the research ethics committees of most of the analyzed studies approved the use of control/placebo groups for the performance of CTs that did not explore new therapeutic alternatives. In some cases, the CT protocols were not approved by ethics committees, nor was informed consent used. In the LMI countries, a shorter period of recruitment was observed for patients who attended universities and public hospitals. Likewise, most of the CTs reviewed had public funding, a significant amount of which came from the pharmaceutical industry. Only one CT reported the low economic and educational level of its participants. Furthermore, none of the authors of the reviewed CTs declared conflicts of interest. Although the axiology of techno-science always takes into account at least the epistemic, technical and economic value systems, the hegemony of the economic values imposed by the pharmaceutical industry is evident in the performance of CTs investigating the treatment of periodontitis in LMI countries.